Anti-NKG2D single domain-based antibodies for the modulation of anti-tumor immune response. (1st January 2021) - Raynaud, Adeline; Desrumeaux, Klervi; Vidard, Laurent; Termine, Elise; Baty, Daniel; Chames, Patrick; Vigne, Emmanuelle; Kerfelec, Brigitte
ABSTRACT: The natural killer group 2 member D (NKG2D) receptor is a C-type lectin-like activating receptor mainly expressed by cytotoxic immune cells including NK, CD8 + T, γδ T and NKT cells and in some pathological conditions by a subset of CD4 + T cells. It binds a variety of ligands (NKG2DL) whose expressions is finely regulated by stress-related conditions. The NKG2DL/NKG2D axis plays a central and complex role in the regulation of immune responses against diverse cellular threats such as oncogene-mediated transformations or infections. We generated a panel of seven highly specific anti-human NKG2D single-domain antibodies targeting various epitopes. These single-domain antibodies were integrated into bivalent and bispecific antibodies using a versatile plug-and-play Fab-like format. Depending on the context, these Fab-like antibodies exhibited activating or inhibitory effects on the immune response mediated by the NKG2DL/NKG2D axis. In solution, the bivalent anti-NKG2D antibodies that compete with NKG2DL potently blocked the activation of NK cells seeded on immobilized MICA, thus constituting antagonizing candidates. Bispecific anti-NKG2DxHER2 antibodies that concomitantly engage HER2 on tumor cells and NKG2D on NK cells elicited cytotoxicity of unstimulated NK in a tumor-specific manner, regardless of their apparent affinities and epitopes. Importantly, the bispecific antibodies that do not compete with ligands binding retained their full cytotoxic activity in the presence of ligands, a valuable property to circumvent immunosuppressive effects induced by soluble ligands in the microenvironment.